The Effect of Job Training, Work Discipline and Compensation on Employee Performance at the Railway Depot during the Covid-19 Pandemic: Pengaruh Pelatihan Kerja, Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan Pada Dipo Kereta Api pada Masa Pandemi Covid-19 - Mashuri, Muchamad Ali; Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the effect of job training, work discipline and compensation partially (individually) and simultaneously (together) on employee performance at the Sidotopo train depo. The approach used in this research is quantitative, which is an approach based on the results of the answers to the questionnaires that have been distributed. The sampling technique used was the saturated sample technique with 37 respondents. The data analysis technique used multiple linear regression, validity test, reliability test, classical assumption test, partial test, simultaneous test of multiple correlation coefficient test, and multiple determination test of respondents with software SPSS version 24 software. The results of this study state that job training has a significant effect on employee performance, work discipline has a significant effect on employee performance, compensation has a significant effect on employee performance, and job training, work discipline, compensation simultaneously (simultaneously) affect employee performance.